Hidden Markov model (HMM) using English voice modality in text editor / Mohamad Hallmi Mohamad Radzhi - Mohamad Radzhi, Mohamad Hallmi (2006)
The current Text Editor (Word Processor) gives problem to those handicap people with physical disorder to use it. They face difficulties on typing word and navigating men uicon by traditionally using mouse device. Some cases, this handicap people have physica llimitation and others have difficulty with the mechanics of writing. Therefore the objective of this thesis is to develop handicap text editor by following concept of Hidden Markov Model (HMM) using English Voice Modality (speech recognition) of a quest for help handicap people using the Text Editor (word processor). The project covers on developing voice-assisted text editor. To see the view more clear, simple prototy pedeveloped to enhance Text Editor (Word Processor) system controlled by using Voice Modality by using middleware application name Dragon NaturallySpeaking. This prototype application is tested using Microsoft Visual Basic 2008 Express Edition. The component or the modules are developed to demonstrate Text Editor receive input by Voice Modality technique. Handicap people can do typing and navigate menu icon by their voice through microphone.